A capacitive bioelectrode for recording electrophysiological signals - Moreno-García, E.; Mújica-Ascencio, S.; de la Rosa-Vázquez, J. M; Stolik-Isakina, S. (Revista Cubana de Física, 2013)
In this paper we describe a gel-free sensor with on-board electrode design, which capacitive couples to the skin to detect the electrical activity in the body. The integrated sensor is manufactured on a standard printed circuit board within 2.2 cm diameter enclosure that can operate through fabric or other insulation. The electrode includes amplification (60 db gain) and passive bandpass filtering (0.5 to 100 Hz). Active shielding surrounding the sensor plate is used to reduce noise pickup. The input referred noise, measured over the electrode bandwidth is 4 μVrms at 0.2 mm sensor distance, and 16 μVrms at 1.2 mm distance trough two cotton cloths. The bioelectrodes were coupled to the scalp trough hair for EEG signals (with 80 db gain), and coupled to the chest through clothing for ECG signals. The recorded signals show well performance of the designed bielectrode.